Epilepsy and abnormal electroencephalogram in children with autism spectrum disorder - Daisy, S; Mohammad, QD; Alam, B; Hoque, A; Haque, B; Rahman, KM; Khan, SU (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):264-6. The abstract of this article is available on the PubMed website